Effect Of Tamarindus Indica L. Pulp On Environmentally Exposed Fluorotic Cattle - Sethi, S.; Senapati, S.K.; Patra , R.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present experiment was carried out in fluorotic cattle environmentally exposed to fluorine emission to assess the effect of Tamarindus Indica L. dried pulp at the dose rate of 100 gm/adult cattle of 4-6 years old. Dried powder of tamarind pulp was fed orally for a continuous period of sixty days. Fluoride level in plasma, urine and faecal sample was monitored on day 0, day 30 and day 60 of this experiment. The treatment resulted in gradual reduction of plasma and urine fluoride level significantly along with significant increase in the excretion of fluoride through faeces. The plasma alkaline phosphatase activity has reduced significantly on both day 30 and day 60.